Determination of Accomplice of Network Pyramid Selling Crime - Haiting Liu; Lixuan Huang (Studies in Law and Justice, 2023)
Due to the particularity of the network itself, the form of the accomplice of the network pyramid selling crime is more complex, showing new characteristics of stronger concealment, faster spreading speed and lower crime cost. The initial organizer and leader of the establishment of the network pyramid selling organization and the expanded organizer and leader of the new level after joining the network pyramid selling organization should bear the corresponding criminal responsibility according to their position and role in the network pyramid selling organization; As for the behavior of network service providers and network technology supporters providing network services and technical support for network pyramid selling crimes, the joint Crime of Organizing or Leading the Pyramid Selling Activities or the Crime of Illegally Using Information Networks and other information network crimes shall be distinguished according to the specific circumstances.